Matching in the housing market with risk aversion and savings - Essi Eerola; Niku Määttänen (The Research Institute of the Finnish Economy (ETLA), 2013)
Abstract:We develop a model of the housing market that features both financial and matching frictions. In the model, risk-averse households may save or borrow in order to smooth consumption over time and finance owner housing. Each household either rents or owns its house. Some renter households become dissatisfied with rental housing and want to buy a house. Prospective sellers and buyers meet randomly and bargain over the price. We show how the outcome of the bargaining process depends on buyer's and seller's asset positions. The results also illustrate how financial frictions magnify the effects of matching frictions. For instance, because of the borrowing constraint, some matches do not result in trade and identical houses are traded at different prices.
Keywords: E21; R21; C78; 330; housing; matching; house prices